Burundi : Staff Report for the 2002 Article IV Consultation and Use of Fund Resources-Request for Post-Conflict Emergency Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper assesses Burundi's 2002 Article IV Consultation and a Request for Post-Conflict Emergency Assistance. Implementation of a Staff-Monitored Program in 2001 was hampered by continued instability and a consequent holding back of donor support. Fiscal performance weakened in the latter part of 2001, mainly reflecting expenditure overruns. The external current account deficit also worsened, and the overall balance of payments was financed by a drawdown of official reserves and a buildup of external debt arrears. The program for the remainder of 2002 and the first half of 2003 focuses on key short-term stabilization measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet